(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Colorectal anastomotic leakage (CAL) is a major postoperative complication associated with significant morbidity and mortality. Early detection remains challenging due to nonspecific clinical signs. C-reactive protein (CRP), an acute-phase reactant, has emerged as a potential biomarker for early prediction of CAL. Aim: To evaluate the role of postoperative CRP levels in predicting colorectal anastomotic leakage and to determine its diagnostic accuracy. Methods: This prospective observational study included 51 patients undergoing colorectal anastomosis. Postoperative CRP levels were measured, particularly on Day 4, and correlated with the occurrence of anastomotic leakage and other complications. Statistical analysis included Chi-square test, logistic regression, Mann–Whitney U test, and ROC curve analysis. Results: Anastomotic leakage occurred in 9 patients (17.6%). No significant association was found between leakage and gender, disease etiology, or surgical technique (p > 0.05). CRP levels were significantly associated with prolonged hospital stay (p = 0.02) and postoperative complications (p = 0.01). ROC analysis demonstrated excellent diagnostic accuracy of Day 4 CRP, with an AUC of 0.964, sensitivity of 88.9%, and specificity of 88.1% at a cut-off value of 154 mg/L. Conclusion: Postoperative CRP is a reliable, cost-effective, and easily accessible biomarker for early prediction of colorectal anastomotic leakage. Routine monitoring can aid in early diagnosis, reduce complications, and optimize postoperative management.